If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 70 = -5(6y + 4) Reorder the terms: 70 = -5(4 + 6y) 70 = (4 * -5 + 6y * -5) 70 = (-20 + -30y) Solving 70 = -20 + -30y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '30y' to each side of the equation. 70 + 30y = -20 + -30y + 30y Combine like terms: -30y + 30y = 0 70 + 30y = -20 + 0 70 + 30y = -20 Add '-70' to each side of the equation. 70 + -70 + 30y = -20 + -70 Combine like terms: 70 + -70 = 0 0 + 30y = -20 + -70 30y = -20 + -70 Combine like terms: -20 + -70 = -90 30y = -90 Divide each side by '30'. y = -3 Simplifying y = -3
| 2x+3=-4x+21 | | 45+61x+4=2 | | 0.10(x+5.00)=2.4 | | -7-5x+6=-18x+13-5x | | 500+35x=55 | | 15+0.75x+13=0.50 | | -8-3x+5=-14x+3-3x | | (2x-3)(x-1)= | | 3(3c-1)-6=7c+7 | | 2x+3x=-4+21 | | 5(x^3+2)+11=59 | | 22+6x+5=12 | | -5-5x+3=-18x+6-5x | | 400=lw*5 | | 0.14(y-5)+0.12y=0.10y-0.05(30) | | (4p^3+8p^2-6)+(2p^3-8p+9)= | | -2+y+19=4y+23 | | 15+75x=13-0.75x | | -5m+39-6(m-2)=8m-(3m-7)-9m+9 | | log(x^2+11x+4)=3 | | 1+0.80-2=0.75 | | 30+22x=80 | | 15x=4x+88 | | 7v-3=6v+4 | | 7x+3-8x=6 | | 2x-4(-x+5)=y | | 14+2x=1.50 | | 16f=1600 | | 6x+2=6x-7 | | 35-25=40 | | 35x+25x=49 | | -1=11-3y |